Análisis de la colaboración público-privada en el sector de los servicios sociales en Gipuzkoa: el modelo guipuzcoano de concertación con el tercer sector a debate (Analyisis of PPPs in the social care sector in Gipuzkoa: debate of the Gipuzkoan model...) - Felix Arrieta Frutos; Enekoitz Etxezarreta Etxarri (Oñati Socio-Legal Series, 2012)
This article analyzes the relationship between international reference frameworks that focus on PPP in relation to the third sector and their effect on Gipuzkoa’s social care system. That is to say, to understand the reality of the relationship between the third sector and the public sector focusing on legal regulation and comparing it with the implemented reality. In this way, we question the existence of what is known as the ‘guipuzcoan model of social care’ that is characterized by a high private participation but contracted by the public administration. Comparing the three historic territories of the CAPV with international reference framework, we can conclude that none of them adjusts to any reference model, and that in fact, the models, even though valid for guidance, are not applied in any of the studied territories.